Role of Peripheral Immune Cells for Development and Recovery of Chronic Pain - Bethea, John R.; Fischer, Roman (Frontiers in Immunology, 2021)
Chronic neuropathic pain (CNP) is caused by a lesion or disease of the somatosensory nervous system. It affects approximately 8% of the general population and negatively impacts a person’s level of functioning and quality of life. Its resistance to available pain therapies makes CNP a major unmet medical need. Immune cells have been shown to play a role for development, maintenance and recovery of CNP and therefore are attractive targets for novel pain therapies. In particular, in neuropathic mice and humans, microglia are activated in the dorsal horn and peripheral immune cells infiltrate the nervous system to promote chronic neuroinflammation and contribute to the initiation and progression of CNP. Importantly, immunity not only controls pain development and maintenance, but is also essential for pain resolution. In particular, regulatory T cells, a subpopulation of T lymphocytes with immune regulatory function, and macrophages were shown to be important contributors to pain recovery. In this review we summarize the interactions of the peripheral immune system with the nervous system and outline their contribution to the development and recovery of pain.